2012
DOI: 10.1007/s00198-012-1958-1
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the development of guidelines for the management of glucocorticoid-induced osteoporosis

Abstract: Guidance for glucocorticoid-induced osteoporosis is updated in the light of new treatments and methods of assessment. National guidelines derived from this resource need to be tailored within the national healthcare framework of each country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
217
0
26

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(243 citation statements)
references
References 160 publications
0
217
0
26
Order By: Relevance
“…Comparing our results to those in other population-based cohorts, we think our results are conservative estimates of GIO risk and recommended treatment in the US (12)(13)(14)(15). The International Osteoporosis Foundation (IOF) and European Calcified Tissue Society (ECTS) working group (IOF-ECTS) and the Brazil Society for Rheumatology released GIO recommendations in 2012 with the European League Against Rheumatism (EULAR) in 2013 (49,50,51). All 4 guideline statements utilize glucocorticoid dose and duration for treatment recommendations, while the ACR, IOF-ECTS, and EULAR guidelines also use the FRAX 10-year risk of major osteoporotic fracture in their treatment determinations (30,49,50,51).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Comparing our results to those in other population-based cohorts, we think our results are conservative estimates of GIO risk and recommended treatment in the US (12)(13)(14)(15). The International Osteoporosis Foundation (IOF) and European Calcified Tissue Society (ECTS) working group (IOF-ECTS) and the Brazil Society for Rheumatology released GIO recommendations in 2012 with the European League Against Rheumatism (EULAR) in 2013 (49,50,51). All 4 guideline statements utilize glucocorticoid dose and duration for treatment recommendations, while the ACR, IOF-ECTS, and EULAR guidelines also use the FRAX 10-year risk of major osteoporotic fracture in their treatment determinations (30,49,50,51).…”
mentioning
confidence: 49%
“…The International Osteoporosis Foundation (IOF) and European Calcified Tissue Society (ECTS) working group (IOF-ECTS) and the Brazil Society for Rheumatology released GIO recommendations in 2012 with the European League Against Rheumatism (EULAR) in 2013 (49,50,51). All 4 guideline statements utilize glucocorticoid dose and duration for treatment recommendations, while the ACR, IOF-ECTS, and EULAR guidelines also use the FRAX 10-year risk of major osteoporotic fracture in their treatment determinations (30,49,50,51). In 2013 the National Osteoporosis Guidelines Group (NOGG) in the UK released guidelines using the IOF-ECTS guidelines for Europe (52).…”
mentioning
confidence: 99%
“…A meta-analysis of 7 large prospective multinational cohorts showed that ever use of corticosteroids was associated with a 66% higher relative risk of osteoporotic fracture compared with never use of corticosteroids (5). The contribution of glucocorticoid use to osteoporosis has also been highlighted in several professional recommendations (24)(25)(26)(27). Conversely, in the context of chronic inflammatory disease, it may be that controlling inflammation can lower the risk of inflammatory bone loss.…”
Section: Effect Of Steroids and Tnf Inhibitors On Bmdmentioning
confidence: 99%
“…In 2012, the Joint IOF -European Calcified Tissue Society (ECTS) Glucocorticoid-induced Osteoporosis Guidelines Working Group published a framework for the development of guidelines for the management of GC-induced osteoporosis [94]. This comprehensive framework reviewed the epidemiology of GCinduced osteoporosis and fracture risk assessment based on 10-year probabilities ascertained from FRAX ® .…”
Section: Osteoporosis Induced By Medicinesmentioning
confidence: 99%